Participatory Communication of Batam City SMEs in Supporting Tourism Development - Fitriyani, Lamria Raya; Rachmawati, Dewi (Institut Komunikasi dan Bisnis LSPR, 2024)
Seeing the current development of the Covid-19 pandemic, the government has again changed its policies in various sectors, including MSME activities and tourism. One of them is the city of Batam which has reopened tourism for both local and foreign tourists. BPS stated that the tourism sector has collapsed. Based on Bappenas data, tourism to Indonesia's GDP is around 4 percent per year. Batam City has opened tourism between countries through a travel bubble, which is an agreement between countries that allows international air travel by reducing restrictions or with applicable provisions. The focus of this study is to examine the participatory communication of MSME actors in the city of Batam in developing its tourism. Tufte & Mefalopulus stated that participatory communication is a dialogical and horizontal communication approach, by identifying problems and finding solutions so that in implementing the strategies that have been discussed. The data collection technique in this study was through interviews with MSME actors. The results of the study showed that participatory communication allows MSME actors to find solutions in dialogical communication to be able to develop tourism.